Hai Thach - Moc Tinh, high pressure/high temperature fields in the first ten years of production Hai Thach - Moc Tinh: Ten years of production, and solutions to maintain and increase its output in the coming period - Pham, Tien Dung; Hoang, Minh Hai; Tran, Vu Tung; Hoang, Ky Son; Vu, Dinh Thi; Nguyen, Quan Phong (Petrovietnam Journal, 2024)
Based on the relevant technical and engineering data, the article presents the main geological and geophysical characteristics of the field cluster of Hai Thach - Moc Tinh, and summarizes its development and production management to date. After 10 years putting the Hai Thach - Moc Tinh cluster into operation under particularly complex conditions, Bien Dong Petroleum Operating Company (Bien Dong POC) has achieved important results, including: (i) Building and developing a simulation model to optimize production operations; (ii) Applying advanced well completion techniques suitable for high pressure and high temperature conditions; regularly conducting technical improvements throughout the operation and maintenance process; (iii) Minimizing the impact of liquid banking near the well bottom, limiting sand production and water encroachment in the wells and exploitation system, increasing reservoir water treatment capacity; (iv) Studying to propose potential locations for infill, sidetrack and multi-lateral wells for improving recovery rate, extending the field lifetime while also serving as a basis to expand the exploration in the area. Despite these achievements, Bien Dong POC is facing the decline of the field’s output and recovery rate due to fluid banking near the well bottom, water encroachment and sand production. Therefore, adjusting the field development plan and accelerating expanded exploration are the solutions to maintain and increase the field’s output in the coming time.